Long intergenic non-coding RNA 00467 promotes lung adenocarcinoma proliferation, migration and invasion by binding with EZH2 and repressing HTRA3 expression - Wang, Xianghai (Mol Med Rep, 2019)
Long non-coding RNAs (lncRNAs) have been identified to serve an important role in the occurrence, development and metastasis of tumours. However, the role of linc00467 in lung adenocarcinoma (LAD) is unclear. In the present study, it was demonstrated that linc00467 expression was upregulated in human lung tumour tissues compared with normal tissues. In addition, high levels of linc00467 expression were associated with larger tumour sizes and later TNM stages. Functional experiments suggested that linc00467 promoted LAD cell proliferation, migration and invasion, and inhibited apoptosis in vitro. Knockdown of linc00467 altered the expression of downstream genes, including HtrA serine peptidase 3 (HTRA3), and RNA immunoprecipitation and chromatin immunoprecipitation assays indicated that linc00467 recruited EZH2 to the HTRA3 promoter to inhibit its expression. Taken together, the results of the present study indicated that linc00467 served an oncogenic role in LAD tumourigenesis, suggesting that it may be used as a novel diagnostic biomarker and therapeutic target for LAD.